1999
DOI: 10.1038/sj.pcan.4500305
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and cellular biology of prostate cancer—the role of apoptosis as a target for therapy

Abstract: Despite the high incidence and mortality rate of prostate cancer, the molecular mechanisms underlying the progression of the disease remain to be fully elucidated. This paper reviews the current state of knowledge on prostatic carcinogenesis, focusing not only on the molecular genetics of prostate cancer, but also on the role of oncogenes, tumour suppressor genes, and growth factors. The remarkable ability of prostate cancer cells to survive androgen withdrawal and apoptosis are discussed, with particular emph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 127 publications
(161 reference statements)
0
4
0
Order By: Relevance
“…Endogenous cannaboids play an important role in the neuronal control of the digestive tract [98], and Izzo and Coutts have suggested that the pharmacological administration of cannaboids, which, in part, act through TRPV1 channels could be used to treat colon cancer [98].As discussed above, TRPM8 is expressed in prostate cancer cells, its expression decreases as the cancer progresses to a more metastatic state, and hence TRPM8 is considered potentially useful for both the diagnosis of prostate cancer and as a target for cancer therapy. The treatment of prostate cancer would be greatly enhanced by better prediction of the course of the disease, including the likelihood of the development of androgen insensitivity and metastases, and by new strategies to kill androgen-insensitive prostate cancer cells which, as mentioned above, are resistant to apoptosis[78][79][80].…”
mentioning
confidence: 99%
“…Endogenous cannaboids play an important role in the neuronal control of the digestive tract [98], and Izzo and Coutts have suggested that the pharmacological administration of cannaboids, which, in part, act through TRPV1 channels could be used to treat colon cancer [98].As discussed above, TRPM8 is expressed in prostate cancer cells, its expression decreases as the cancer progresses to a more metastatic state, and hence TRPM8 is considered potentially useful for both the diagnosis of prostate cancer and as a target for cancer therapy. The treatment of prostate cancer would be greatly enhanced by better prediction of the course of the disease, including the likelihood of the development of androgen insensitivity and metastases, and by new strategies to kill androgen-insensitive prostate cancer cells which, as mentioned above, are resistant to apoptosis[78][79][80].…”
mentioning
confidence: 99%
“…The onset and progression of cancer is characterized by cell cycle dysregulation, leading to enhanced cell growth, concomitant with suppression of mechanisms responsible for cell death (1)(2)(3)(4). Notably, dysregulated homeostasis of intracellular Ca 2+ is involved in cancer.…”
Section: Introductionmentioning
confidence: 99%
“…For example, ligand binding to several membrane receptors triggers a series of events, leading to the activation of phospholipase C (PLC) and synthesis of inositol-1,4,5-trisphosphate (Ins(1,4,5)P3). Ins (1,4,5)P3 opens the Ins (1,4,5)P3 receptor (IP3R), which is an intracellular ion channel and expressed mostly in the endoplasmic reticulum, resulting in the release of Ca 2+ from the endoplasmic reticulum (7,8). Ca 2+ signals in the form of spikes, oscillations or waves are spatially and temporally tightly regulated (9) to avoid prolonged intracellular elevation of Ca 2+ that is toxic and lethal for cells (10).…”
Section: Introductionmentioning
confidence: 99%
“…Contradictions as to the direct role of TP53 in prostate cancer abound in the literature, but TP53 mutations appear to be more common in high-grade, metastatic and androgen-independent human prostate cancer (Bookstein et al, 1993; Chi et al, 1994; Costa-Pereira and Cotter, 1999; Gumerlock et al, 1997; Meyers et al, 1998). …”
Section: Introductionmentioning
confidence: 99%